Penerapan Teknologi Produksi Jagung Melalui Pendekatan Pengelolaan Tanaman Terpadu Pada Lahan Sawah Tadah Hujan - margaretha, margaretha; Syuryawati, Syuryawati (Jurnal Penelitian Pertanian Tanaman Pangan, 2017)
Corn production technology development through the approach of Integrated Crop Management (ICM) has been implemented in the village Mandalle, District Mandalle, Pangkep, South Sulawesi from 2005 to 2008. In 2009 in daearah development conducted research to determine the level of corn production technology application in paddy field rainfed and socio-economic impact on local communities, particularly farmers who are engaged in research and development. The results showed that of the nine components of the technology are socialized at the farm level, only fertilizers and spacing have not been applied in real time, medium varieties, land preparation, drainage, water supply, weeding, eradication of pests / diseases and the use of tools sheller real effect until very real. In the review of the farmer's perception of the nine components of the product technology of corn, seven of them rated good. Land use after the rice harvest with corn still applied to farmers with a profit of Rp 3,045,354 / ha of hybrid varieties BISI and Rp 4,555,283 / ha of open pollinated varieties Lamuru, thereby increasing farmers' income from 31.0 to 46.7%. In addition to economic benefits, planting corn after harvest of rice in the rainfed areas can also reduce unemployment and urbanization, the formation of social and economic institutions such as land rental services, equipment rental services pipil, partnerships and corn growers group.